On the textbook “Genetic analysis of terrigenous deposits” - V. N. Komarov; S. A. Samokhvalov (Известия высших учебных заведений: Геология и разведка, 2022)
The textbook under review considers the fundamentals of the genetic analysis of terrigenous and associated sediments. A classification scheme of the genetic types, subgroups, groups, and supergroups of these deposits is provided. According to the proposed scheme, continental, transitional, marine, and mixed genetic types are sequentially described. A set of sedimentation features that allow for identification of the genetic type, its lateral and vertical transitions to other genetic types, is introduced. The form and size of modern accumulative bodies formed by genetic types of deposits and their fossil analogues are indicated.